PERANCANGAN IKLAN LAYANAN MASYARAKAT DALAM BENTUK MOTION GRAPHIC TENTANG WAWASAN HIV/AIDS KOTA PAYAKUMBUH - Fauzan Alhaq Bukharla, Dini Faisal, S.Ds., M.Ds., Drs. Yusron Wikarya, M.Pd. (DEKAVE : Jurnal Desain Komunikasi Visual, 2017)
The aimed of designing is to develop media education public service announcements in the form of motion graphic, in order that Payakumbuh society could understand the insights of HIV/AIDS, help broaden the prevention of HIV/AIDS among the age of 20 years - 40 years of Payakumbuh socety, as well as helping the Government city/Payakumbuh Institute in preventing the spread of HIV/AIDS. The methods of design is by interview and documentation, a visit to the Health Office and the Office of National AIDS Commission in Payakumbuh. And the method of data analysis is the 5W1H analysis by reviewing What?, Who?, When?, Where?, Why?, and How? on the design of these. The result of this Public Service Announcements is a Motion Graphic about HIV / AIDS in Payakumbuh, as well as with (media support) a CD Cover, a Poster, a X-banners, a mug, a pins, a cloth, a bracelet, a Buff, and a Snapback.Keyword : Public Service Announcement, Motion Graphic